1962
DOI: 10.1177/070674376200701s09
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacology of Tranylcypromine and Trifluoperazine

Abstract: Tranylcypromine was compared to trifluoperazine in a number of pharmacological test procedures. Both compounds were effective in producing catalepsy, a selective blockade of the conditioned stimulus, and potentiation of hexobarbital-induced sleep. Unlike trifluoperazine, tranylcypromine was very effective as a tryptamine potentiator, a reflection of its activity as an in vivo inhibitor of the enzyme monoamine oxidase. Tranylcypromine was ineffective in producing any appreciable decrease in spontaneous motor ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1965
1965
1974
1974

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…99 No direct experimental evidence for a similar action of tranylcypromine was reported, but animal experiments established that barbiturate sleep time was significantly prolonged after tranylcypromine. 44,168,188 Likewise, a liver microsomal enzyme system which inactivates pethidine ( Demerol) was inhibited by hydrazine MAOI.ll2 Again, direct evidence of a similar action by tranylcypromine was lacking. A single case report showed evidence for a toxic reaction to pethidine in a patient receiving tranylcypromine.…”
Section: Pharmacologic Actionsmentioning
confidence: 99%
“…99 No direct experimental evidence for a similar action of tranylcypromine was reported, but animal experiments established that barbiturate sleep time was significantly prolonged after tranylcypromine. 44,168,188 Likewise, a liver microsomal enzyme system which inactivates pethidine ( Demerol) was inhibited by hydrazine MAOI.ll2 Again, direct evidence of a similar action by tranylcypromine was lacking. A single case report showed evidence for a toxic reaction to pethidine in a patient receiving tranylcypromine.…”
Section: Pharmacologic Actionsmentioning
confidence: 99%
“…the drug first caused a decrease and 1.5-2 h later an increase of the SMA, which lasted for the following 4 -5 h. Van der Schoot et al (11) instead reported that TCP at the dose of 9.8 mg/kg (p.o.) induced an immediate increase of the SMA, Tedeschi et al (10) on the other hand ob served that this drug, in doses up to 20 mg/kg (p.o.) slightly decreased SMA in rats.…”
mentioning
confidence: 99%
“…As to TCP, Tedeschi et al (10) observed that this drug at the dose of 3.4 -8 .6 mg/kg (p.o.) caused a selective blockage of conditioned responses (pole jump).…”
mentioning
confidence: 99%